Perawatan Spiritual Pasien Di Ruang Intensive Care Unit: Narrative Review - Suhartini, Suhartini; Pasole, Fetty Yublika; Sobirin, Mochamad Ali (Universitas Tribhuwana Tunggadewi, 2023)
Nursing services worldwide today strive to incorporate a holistic approach, where individuals are regarded as complete beings encompassing biological, psychological, social, cultural, and spiritual dimensions. Within the context of intensive care units (ICUs), spiritual care is recognized as a fundamental element that can foster hope, provide a sense of life's purpose, and alleviate anxiety in patients. This research aimed to gain insight into the provision of spiritual care for ICU patients and utilized a narrative review methodology. Searches were conducted in clinical databases such as Scopus and ProQuest, using keywords like